Maximum of sum of $k$-th powers with sum of bases equal to $n$

For some positive integer constants $n, k$ and $t$, I want to find the values for $n_1, \ldots, n_t$, all positive integers, that maximize the following sum :

$$\sum_{i = 1}^t (n_i)^k$$

such that $n_i \geq 1$ for each $i$ and $\sum_{i = 1}^t n_i = n$. So, what's the best way to pick the $n_i$'s ?

It feels like the right choice is to let $n_1 = n - t + 1$ and $n_2 = n_3 = \ldots = n_t = 1$. But my attempts to prove this go through a lot of tedious steps, though this seems simple enough. So, does anyone have a proof for this ?

EDIT :

In the event someone has the same question, here's the proof, following answerer's advice.

Let's try induction on $t$ (assuming $t < n$). I want to show that $\sum_{i = 1}^t (n_i)^k \leq (n - t + 1)^k + t - 1$. True for $t = 1$, base case covered. Now,

$$\sum_{i = 1}^t (n_i)^k = \sum_{i = 1}^{t - 1} (n_i)^k + n_t^k \leq (n - n_t - t + 2)^k + t - 2 + n_t^k$$

by induction. Letting $n_0 = n - n_t -t +2$, we get another sum of the same type with $t = 2$:

$$n_0^k + n_t^k + t - 2 \leq (n_0 + n_t - 2 + 1)^k + (2 - 1) + t - 2 \\ = (n - n_t - t + 2 + n_t - 2 + 1)^k + t - 1\\ = (n - t + 1)^k + t - 1$$

I think your intuition is correct for the solution (for $k>1$), and I would prove it by considering $t=2$ and then using an inductive argument for any $t$ up to $n-1$.